PENGGUNAAN BAHAN AJAR CERITA ANAK SEBAGAI MEDIA ALTERNATIF PADA PEMBELAJARAN SASTRA ANAK KELAS VI DI SDN 13 LABUAN - Anizar, Lis; Nur, Yunidar; Harisah, Sitti (BAHASANTODEA, 2017)
This study describes the use of printed teaching material and audio visual learning in children's literature in elementary school. The problems studied are (1) How is the use of children's story teaching material as an alternative media for learning literature on children in class VI in SDN 13 Labuan? (2) How is the effectiveness of story teaching material for children as an alternative media on literature instructional on children in grade VI at SDN 13 Labuan?. The research aims to describe the use of teaching material and describe the effectiveness of children’s story teaching material as an alternative media on literature instructional on children in grade VI at SDN 13 Labuan. The method used was descriptive qualitative with data collection covering observation, interview, and written test. The data analysis was begun with data collection, data reduction, data display, and drawing conclusion. The research findings show that the use of teaching materials as an alternative media on literature instructional is printed teaching material or local story book and audiovisual teaching material as an alternative are effective. Based on the evaluation, score number of audiovisual media use is 1462 with the average 86 and achieved 82.3% while the use of printed teaching material got score 1436 with the average 84 and achieved 76.4%. The results were obtained from 17 students at SDN 13 Labuan who all students stated passed as the satndard of minimum achievement criteria required in the school. Therefore, it can e concluded that the use of children’s story teaching material through printed teaching material and audiovisual teaching material as the alternative media on literature instructional of the children in grade VI at SDN 13 Labuan are effective to use especially on literature instructional of the children based on the results of the students’ outcomes who achieved minimum achievement criteria.